Transverse Myelitis Following SARS‐CoV ‐2 Vaccination: A Pharmacoepidemiological Study in the World Health Organization's Database - Nguyen, Sophie; Bastien, Etienne; Chrétien, Basile; Sassier, Marion; Defer, Gilles; Nehme, Ahmad; Lelong‐Boulouard, Véronique; Alexandre, Joachim; Fédrizzi, Sophie; Morice, Pierre‐Marie (Annals of Neurology, 2022)
BACKGROUND: Transverse myelitis (TM) has recently been associated by health authorities with Ad26.COV2.S (Janssen/Johnson & Johnson), one of the 5 US Food and Drug Administration (FDA) or European Medicines Agency (EMA) labeled severe acute respiratory syndrome-coronavirus 2 (SARS-CoV-2) vaccines. It is unknown whether a similar association exists for the other FDA or EMA labeled SARS-CoV-2 vaccines (BNT162b2 [Pfizer/BioNTech], mRNA-1273 [Moderna], ChAdOx1nCov-19 [Oxford-AstraZeneca], and NVX-CoV2373 [Novavax]). This study aimed to evaluate the association between SARS-CoV-2 vaccine class and TM. METHODS: This observational, cross-sectional, pharmacovigilance cohort study examined individual case safety reports from VigiBase, the World Health Organization's pharmacovigilance database. We first conducted a disproportionality analysis with the information component (IC) using the reports of TM that occurred within 28 days following exposure to the FDA or EMA labeled SARS-CoV-2 vaccines, from December 1, 2020 (first adverse event related to a SARS-CoV-2 vaccine) to March 27, 2022. Second, we analyzed the clinical features of SARS-CoV-2 vaccine-associated TM cases reported in VigiBase. RESULTS: = 0.52) SARS-CoV-2 vaccines that are authorized by the FDA or the EMA. CONCLUSIONS: Findings from this observational, cross-sectional pharmacovigilance study showed that mRNA-based and vector-based FDA/EMA labeled SARS-CoV-2 vaccines can be associated with TM. However, because TM remains a rare event, with a previously reported rate of 0.28 cases per 1 million vaccine doses, the risk-benefit ratio in favor of vaccination against SARS-CoV-2 virus remains unchallenged. Rather, this study suggests that clinicians should consider the diagnosis of TM in patients presenting with early signs of spinal cord dysfunction after SARS-CoV-2 vaccination. ANN NEUROL 2022;92:1080-1089.